2018
DOI: 10.1111/jeb.13277
|View full text |Cite
|
Sign up to set email alerts
|

The influence of developmental environment on courtship song in cactophilic Drosophila

Abstract: Closely related species often differ in the signals involved in sexual communication and mate recognition. Determining the factors influencing signal quality (i.e. signal's content and conspicuousness) provides an important insight into the potential pathways by which these interspecific differences evolve. Host specificity could bias the direction of the evolution of sexual communication and the mate recognition system, favouring sensory channels that work best in the different host conditions. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Particularly interesting are those that regulate wing development since they may account for phenotypic syndromes, like abnormalities in wing morphology and venation reported in both D. buzzatii and D. koepferae reared in alternative hosts and alkaloids-containing media [ 38 ]. Moreover, along with DEGs linked to flight behaviour like Gpdh , genes involved in wing development offer a plausible explanation for courtship-song plasticity induced by rearing cacti [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly interesting are those that regulate wing development since they may account for phenotypic syndromes, like abnormalities in wing morphology and venation reported in both D. buzzatii and D. koepferae reared in alternative hosts and alkaloids-containing media [ 38 ]. Moreover, along with DEGs linked to flight behaviour like Gpdh , genes involved in wing development offer a plausible explanation for courtship-song plasticity induced by rearing cacti [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we address these issues by investigating how the wing has evolved in twelve populations of the cactophilic species Drosophila buzzatii raised in commongarden conditions and using an isofemale line design. Only the males of the D. buzzatii species use wings to produce a courtship song (Iglesias & Hasson, 2017;Iglesias et al, 2018a;Iglesias, Soto, Soto, Colines, & Hasson, 2018b), and a previous study has shown a rapid divergence of courtship song parameters among these populations (Iglesias et al, 2018a). Thus, we first investigated whether the wings of males and females are evolving differently among the sampled populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although both species prefer different cactus species as oviposition sites suggesting a certain degree of specialization, they can be recovered from the same rotting pockets in sympatric areas, demonstrating a partial niche overlap (Soto et al, 2012). Many studies have shown that performance, measured through various fitness-related traits, depends greatly on the breeding resource (Hasson et al, 2009;Hurtado et al, 2012;Soto et al, 2012Soto et al, , 2018Iglesias et al, 2018;Bouzas et al, 2021). Overall, D. buzzatii has higher fitness (higher viability, faster development, larger adult body size, higher resistance to starvation, and increased mating success) when grown in the decaying cladodes of Opuntia sulphurea (G Don ex Loudon) than in the columnar Trichocereus terscheckii (J Parm.…”
Section: Introductionmentioning
confidence: 99%